How sustainable is tuna aquaculture? A methodology to assess the sustainability of seafood production systems - Guillen, Jordi; Asche, Frank; Carvalho, Natacha; Druon, Jean-Noël; Llorente, Ignacio; Sciberras, Andrew; Višnić Novaković, Svjetlana; Vukov, Ivana (Frontiers in Aquaculture, 2024)
Considering the need to feed the increasing world population, it is essential to ensure that food production systems are sustainable. Aquaculture has been identified as a potential crucial source of sustainable food with its significant potential for future growth, notably by the recent EU regulations aiming at boosting food security and sustainable food systems. In this context, it is important to reflect on how the aquaculture of carnivorous species, which are exhibiting the highest growth rates, stands in respect of environmental impacts and contribution to the overall food supply. In particular, tuna aquaculture has been largely criticized for its high environmental impacts and general low sustainability. Here, we present a methodology to assess the sustainability of seafood production systems, with a first analysis applied to Atlantic bluefin tuna (BFT) aquaculture, detailed for both BFT fattening and farming. Results suggest that the limited economic and social contributions of BFT aquaculture do not currently compensate its environmental impacts with an estimate of a 3.4-fold higher long-term social cost than the short-term economic gain. However, it is also a species where the production cycle is not closed in commercial operation, and with a significant potential for further improvement as the control of the production process increases.